Learning to visualize data with D3.js - Hernandez, Rafael (Infinite Skills, 2014)
"In this Learning to Visualize Data with D3.js training course, expert author Rafael Hernandez teaches you how to build data visualizations with the D3 JavaScript library. This course is designed for users that already have some HTML, CSS, and JavaScript programming experience. You will start by learning the basics of D3, including how to bind data from JavaScript arrays to elements, scale data, and style simple data visualizations with CSS. From there, Rafael will show you how to introduce interactivity into your data visualization, including how to add a sort button, animate changes, and respond to other mouse events. This video tutorial will also cover how to create a line chart and a scatter-plot data visualization. "--Resource description page.